(WO)MAN IN THE MIRROR — A REFLECTION: LAW’S INFLUENCE ON SOCIETY, IDENTITY AND FEMINISM (The Pretoria Student Law Review, 2021)
A legal system, which proposes one thing while implementing another, lacks integrity and accountability – values the Constitution aims for the South African legal system to uphold. I propose that a more open approach to the law will result in a legal system that provides for true freedom in dignity and identity for those falling under its jurisdiction. Furthermore, moving away from a modernist approach to a post structural, more general jurisprudence will lead to inclusion of women (providing a remedy to their oppression) and to a more substantially equal application of the law. I will be structuring my research around the work of a couple theorists and will use their perspectives to supplement my own argument. These include the work of Marx, Foucault, Veitch, Barnett, de Beauvoir, Dowling, Botha and Douzinas and Geary. To add flavour to this investigation, I will include some neuro-scientific perspectives based on the work of David Rock. Veitch suggests that the law plays a large role in protecting the autonomy of the individual — an area of great neuro-scientific research.
Keywords: legal system; accountability; integrity; general jurisprudence; neuro-scientific perspectives; autonomy of the individual